2021
DOI: 10.1080/26895269.2021.1986191
|View full text |Cite
|
Sign up to set email alerts
|

How the COVID-19 pandemic affects transgender health care - A cross-sectional online survey in 63 upper-middle-income and high-income countries

Abstract: Background Due to the COVID-19 pandemic, access to medical care is restricted for nearly all non-acute conditions. Due to their status as a vulnerable social group and the inherent need for transition-related treatments, transgender people are assumed to be affected particularly severely by the restrictions caused by the COVID-19 pandemic. Methods As an ad hoc collaboration between researchers, clinicians and 23 community organizations, we developed a web-based survey i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…Transgender people in Canada report avoiding care generally (Bauer et al, 2015) and during the pandemic (Tami et al, 2022). This aligns with global findings of a multinational survey of transgender people in 63 upper‐middle‐ and high‐income countries by Koehler et al (2021) who found the pandemic exacerbating the structural vulnerabilities of transgender people.…”
Section: Introductionsupporting
confidence: 90%
“…Transgender people in Canada report avoiding care generally (Bauer et al, 2015) and during the pandemic (Tami et al, 2022). This aligns with global findings of a multinational survey of transgender people in 63 upper‐middle‐ and high‐income countries by Koehler et al (2021) who found the pandemic exacerbating the structural vulnerabilities of transgender people.…”
Section: Introductionsupporting
confidence: 90%
“…[8] There has been no similar study on transgender people in Hyderabad; thus, this study attempted to fill that void. Many studies have been conducted in India and other countries to assess barriers to health-care utilization, accessibility to health-care services by transgender, [9,10] and the impact of COVID-19 on transgender health, [11] but no such studies were conducted in Hyderabad. Above studies did not examine the impact of COVID-19 on transgender individuals health-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Shortages of medications also occurred[ 21 ]. These conditions arrested or hindered gender-transition for many trans persons and caused psychological distress due to the regression to undesired sex features[ 22 ]. Despite the withdrawal of most restrictive measures, much effort is still needed to normalize the situation.…”
Section: Impact Of the Covid-19 Pandemic On Transgender Health Carementioning
confidence: 99%